An analysis of the factors influencing the demand for care in the community for older adults with mild dementia in China: a cross-sectional study - Shuang Teng; Shuxin Xu; Mengmeng Liang; Jingjie Li; Dongdong Shen; Yan Cheng; Xianping Tang (BMC Nursing)
Abstract Introduction The care needs of older adults with mild dementia have not been studied in depth. In this study, we investigated the impairment status of patients with mild dementia and analyzed the care needs of patients with different levels of impairment in terms of activities of daily living, medical services, environmental care, psychological comfort and social participation, and the factors influencing them. Methods This study used a cross-sectional research method to investigate mildly demented older adults aged 60 years and above in the Chinese community. A self-administered questionnaire was used to assess the care needs of mildly demented older adults in terms of daily living, medical services, psychological comfort, home environment and social participation, and the ability level of mildly demented older adults was assessed using the official Chinese Norms for Assessing the Ability of the Elderly (GB/T42195-2022). Independent samples t-test and one-way ANOVA were used to compare the differences between demographic characteristics, impairment levels and care needs. Multiple linear regression analysis was used to analyze the independent factors influencing care needs. Results A total of 267 participants were included in this study and participated in the analyses. The results showed that there were differences in the scores of care needs between different ability levels: mildly impaired (58.74 ± 9.008), moderately impaired (78.45 ± 8.951) and severely impaired (99.67 ± 6.480), and that health care services were the main care needs of older adults with mild dementia, and older adults with mild dementia of different ability levels had high needs for health care services. For activities of daily living and psychological comfort, needs increased significantly with the severity of impairment and decreased with worsening impairment in environmental care and social participation. Comprehensive ability level for older adults: Moderately impaired (β = 0.136, P = 0.012), Severely impaired (β = 0.306, P < 0.001), Age:70-79 years (β = 0.136, P = 0.010), 80 years and above (β = 0.354, P < 0.001), Living with children (β = 0.267, P < 0.001), Living with spouse (β = 0.232, P = 0.003) and participation in sports and exercise (β = 0.162, P = 0.001)) had significant positive effects on community care service needs, drinking alcohol (β = -0.118, P = 0.007), and with other chronic diseases ((β = -0.130, P = 0.004) had significant negative effects on community care service needs. Discussion Factors influencing the community care needs of older people with mild dementia who participated in this study included: comprehensive older adults’ abilities, age, whether accompanied by other chronic diseases, history of alcohol consumption, presence of physical activity. Practical implications Taking into account the different care needs of older adults with mild dementia at different stages of impairment, a comprehensive care program for older adults with mild dementia has been improved in a number of aspects, including daily living, medical services, home environment, psychological well-being and social participation.